Comparative ABO blood group and rhesus factor distribution between homogenous and heterogenous populations in South Eastern Nigeria - Ikechukwu Eugene Onah; Ezinne Veronica Moses; Ifeyinwa Esther Ugwuoke; Sabina Chioma Eze; Jude Ifeanyichukwu Okwor; Patience Obiageli Ubachukwu (Asian Journal of Medical Sciences, 2019)
Background: The ABO blood group and Rhesus (Rh) factor remain the most important blood group in transfusion medicine. Knowledge of ABO and rhesus blood group distribution within a population is indispensable for transfusion medicine, clinical and marriage counselling.